ナンキョク ドーム フジ カンソク キョテン ニオケル ヒョウソウ シンソウ コア クッサク - 藤井, 理行; フジイ, ヨシユキ; 東, 信彦; アズマ, ノブヒコ; 田中, 洋一; タナカ, ヨウイチ; 高橋, 昭好; タカハシ, アキヨシ; 新堀, 邦夫; シンボリ, クニオ; 中山, 芳樹; ナカヤマ, ヨシキ; et al. (国立極地研究所, 1999)
P(論文) 南極ドームふじ観測拠点において, 1993年パイロット孔の掘削とケーシングが行われたのに引き続き, 1995年から2カ年にわたり本格的な深層コア掘削が進められ, 1996年12月に2503.52m深に達した。本掘削におけるコア掘削の総回数は1369回, チップ回収作業は837回に及んだ。1回の平均コア掘削長は1.75m, 一日の平均コア掘削長は8.21mであった。本報告では, 現地で使用された掘削システムの概要とともに, 掘削の経過, および掘削の方法を述べるとともに, 掘削中に生じたさまざまなトラブルについても取られたその対策とともに報告し, 併せて今後の課題を示した。 Deep ice coring was carried out at Dome Fuji Station, Antarctica in 1995 and 1996 following a pilot borehole drilled and cased with FRP pipes in 1993,and reached 2503.52m in December 1996. Total numbers of ice coring runs below the pilot borehole and chip collection were 1369 and 837 respectively. The mean coring depths per run and per day were 1.75m and 8.21m respectively. We report the outline of the coring operation, the system, coring method, and troubles encountered during the coring work. departmental bulletin paper